Masks of conquest : literary study and British rule in India - Viswanathan, Gauri (Oxford India paperbacks., 2015)
A work in postcolonial studies, this text describes the introduction of English studies in India under British rule and illuminates the discipline's transcontinental movements and derivations, showing that the origins of English studies are as diverse and diffuse as its future shape. The text also argues forcefully that the curricular study of English can no longer be understood innocently of or inattentively to the imperial contexts in which the discipline first articulated its mission.